Circulating circular RNAs hsa_circ_0001204 and hsa_circ_0001747 act as diagnostic biomarkers for active tuberculosis detection - Huang, Zikun (Int J Clin Exp Pathol, 2018)
In recent years, increasing evidence has suggested that circRNAs can serve as novel diagnostic markers for many diseases. However, little is known about the value of circRNAs in the diagnosis of active tuberculosis (TB). In this study, 10 circRNAs which we previously found to be involved in Mycobacterium tuberculosis infection were selected as candidate targets for subsequent circulating circRNA assay. Compared with healthy controls, plasma levels of hsa_circ_0001204 and hsa_circ_0001747 were significantly decreased (P < 0.001). Plasma levels of hsa_circ_0001204 and hsa_circ_0001747 were correlated with TB severity. Hsa_circ_0001204 and hsa_circ_0001747 were selected for further analysis in another 145 TB patients and 120 control individuals. The area under the receiver operating characteristic curve (AUC) for distinguishing TB patients was 0.928 (95% confidence interval: 0.897-0.960; sensitivity = 86.21%, specificity = 89.17%) when hsa_circ_0001204 and hsa_circ_0001747 were used in combination. Further evaluation on potential biomarkers showed that hsa_circ_0001204 and hsa_circ_0001747 may specifically identify patients with TB. Additionally, hsa_circ_0001204 and hsa_circ_0001747 plasma levels after treatment were significantly higher than that pre-treatment (P < 0.001). Our present study indicates that circulating hsa_circ_0001204 and hsa_circ_0001747 may represent novel plasma biomarkers for TB diagnosis.